Given that
a
2
+
2
a
c
+
2
b
c
−
b
2
=
1
0
9
2
a
+
2
c
−
b
=
7
Find
a
+
b
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
a^2+2ac+2bc-b^2=(a^2+2ac+c^2)+(ac-ab+c^2-bc)-(ac+c^2-ab-bc)-(c^2-2bc+b^2)=(a+c)^2+(a+c)(c-b)-(a+c)(c-b)-(c-b)^2=((a+c)-(c-b))((a+c)+(c-b))=(a+b)(a+2c-b) Therefore, a+b=1092/7=156
Much simpler:
a 2 − b 2 + 2 a c + 2 b c = ( a + b ) ( a − b ) + 2 c ( a + b )
= ( a + b ) ( a − b + 2 c ) = ( a + b ) ( ( 7 − 2 c ) + 2 c )
= 7 ( a + b ) = 1 0 9 2 ⟹ a + b = 1 5 6
By factorising the first expression: a^2 + 2ac + 2bc - b^2 = 1092 (a + b)(a - b) + 2c( a + b ) = 1092 Hence, (a + b) ( a - b + 2c) = 1092 Notice how a - b + 2c is just the same as the second expression which is known to have the value 7. Now we can simply divide both sides by 7 to obtain the result a + b = 156
Problem Loading...
Note Loading...
Set Loading...
a 2 + 2 a c + c 2 − ( b 2 − 2 b c + c 2 ) = 1 0 9 2
= ( a + c ) 2 − ( b − c ) 2 = 1 0 9 2
= ( a + b ) ( a + 2 c − b ) = 1 0 9 2
thus
a + b = 1 5 6